Impact of Military Actions on Ukraine’s Energy Infrastructure - Tkach, Dmytro (Herald of Economics, 2026)
The article analyzes the multifaceted impact of the full-scale invasion on Ukraine’s energy infrastructure. It examines the scale of physical destruction, financial losses, socio-humanitarian consequences, and key resilience and recovery strategies. The aim of the study is to systematize and analyze empirical data and expert assessments regarding the impact of hostilities, to identify the dynamics of destruction and the effectiveness of adaptation measures, as well as to outline the long-term prospects for rebuilding Ukraine’s energy sector. The study applies general scientific methods: analysis and synthesis (for structuring competencies), induction and deduction (for forming conclusions), comparison (to identify changes between 2024 and 2025), as well as generalization (to establish overall trends). The analytical method was used to assess damages based on data from KSE Institute, the Ministry of Energy, and other open sources. A systematic approach was applied to structure information about physical damage, economic losses, and humanitarian consequences. A comparative analysis method was also used to examine recovery strategies. As of May 2024, the total losses of Ukraine’s energy sector exceeded $56 billion, of which more than $16 billion were direct damages. Over 70% of generating capacities were lost or occupied, including the Zaporizhzhia Nuclear Power Plant and key thermal power plants. Despite this, thanks to colossal recovery efforts and the implementation of physical protection, the energy system demonstrated high resilience, allowing the country to get through heating seasons without a complete blackout. The long-term recovery strategy envisions a fundamental shift from a centralized to a decentralized energy system model, which will enhance its resilience to future threats. Reconstruction is financed by international partners (World Bank, EIB, USAID) and domestic investments, including business lending.